2020
DOI: 10.1530/ec-19-0510
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of a mitotane-resistant adrenocortical cell line

Abstract: Mitotane is the only drug approved for the therapy of adrenocortical carcinoma (ACC). Its clinical use is limited by the occurrence of relapse during therapy. To investigate the underlying mechanisms in vitro, we here generated mitotane-resistant cell lines. After long-term pulsed treatment of HAC-15 human adrenocortical carcinoma cells with 70 µM mitotane, we isolated monoclonal cell populations of treated cells and controls and assessed their respective mitotane sensitivities by MTT assay. We performed exome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 56 publications
(63 reference statements)
3
21
0
Order By: Relevance
“…This also suggests that, in contrast to H295R, MUC-1 favor alternative mechanism(s) of regulation and clearance of intracellular cholesterol, providing a possible escape mechanism from mitotane-induced lipotoxicity. Seidel et al have described similar findings in relation to FC and CE handling in a strain of HAC15 with induced resistance to mitotane (Seidel et al 2020). Detailed evaluation of lipid/cholesterol metabolism in ACC, using the full range of cell lines and banked tumour samples, is necessary to evaluate the significance for development of future therapeutic strategies.…”
Section: :6mentioning
confidence: 70%
“…This also suggests that, in contrast to H295R, MUC-1 favor alternative mechanism(s) of regulation and clearance of intracellular cholesterol, providing a possible escape mechanism from mitotane-induced lipotoxicity. Seidel et al have described similar findings in relation to FC and CE handling in a strain of HAC15 with induced resistance to mitotane (Seidel et al 2020). Detailed evaluation of lipid/cholesterol metabolism in ACC, using the full range of cell lines and banked tumour samples, is necessary to evaluate the significance for development of future therapeutic strategies.…”
Section: :6mentioning
confidence: 70%
“…Symbols: à activation, ┤ inhibition further studies should be performed using in vivo models. 81 This might explain recurrence during and after ACC therapy.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…The study revealed changes in lipoprotein and lipid homeostasis, which may collectively contribute to the characteristics of the resistant phenotype. Because this model evaluated mitotane resistance only in vitro , further studies should be performed using in vivo models 81 . This might explain recurrence during and after ACC therapy.…”
Section: Pharmacological Aspectsmentioning
confidence: 99%
“…The study pointed at the changes in lipoprotein and lipid homeostasis which collectively may contribute to the resistant phenotype. Although this model might help develop strategies to overcome mitotane resistancein vitro , further studies should be performed using in vivo models of mitotane resistance before conducting clinical trials [70].…”
Section: Other Mechanismsmentioning
confidence: 99%